Positioning Rumah Sakit (Studi Kasus di Kecamatan Kemuning) - Murni, Shantri Dewi; Asiati, Diah Isnaini (Universitas muhammadiyah palembang, 2011)
The formulation of the problem in this research is how tne positioning of the hospital in kecamatan kemuning. The goal is fine and analysis the positioning of the hospital. This research is a descriptiv eresearch. The variable in this research is poisitioning the hospital. The indicators are the pysical appereance of building ,equipment fitting, speed of action, friendly nurses, and medical completeness. The primary data is respondent answer to the question. The analytical method is quantitative analysis, kwadran analysis, profile can be seen that Dr.M.Hoesin prominent on the pysical apperence of buildingand equiment fitings measures, for Siti Khadijah prominent of friendliness nurses and the same actor like Rk Charitas.Result from the overall analysis showed that hospital that precies positioning is Dr.M.Hoesin and Rk Charitas while for Siti Khadijah imporer positioning